Loss of Pseudouridine Synthases in the RluA Family Causes Hypersensitive Nociception in Drosophila. Issue 12 (1st December 2020) - Song, Wan; Ressl, Susanne; Tracey, W Daniel
Abstract: Nociceptive neurons of Drosophila melanogaster larvae are characterized by highly branched dendritic processes whose proper morphogenesis relies on a large number of RNA-binding proteins. Post-transcriptional regulation of RNA in these dendrites has been found to play an important role in their function. Here, we investigate the neuronal functions of two putative RNA modification genes, RluA-1 and RluA-2, which are predicted to encode pseudouridine synthases. RluA-1 is specifically expressed in larval sensory neurons while RluA-2 expression is ubiquitous. Nociceptor-specific RNAi knockdown of RluA-1 caused hypersensitive nociception phenotypes, which were recapitulated with genetic null alleles. These were rescued with genomic duplication and nociceptor-specific expression of UAS- RluA-1 -cDNA . As with RluA-1, RluA-2 loss of function mutants also displayed hyperalgesia. Interestingly, nociceptor neuron dendrites showed a hyperbranched morphology in the RluA-1 mutants. The latter may be a cause or a consequence of heightened sensitivity in mutant nociception behaviors.